EFFICIENCY OF COOPERATIVE LANGUAGE LEARNING (Journal of Universal Science Research, 2023)
Cooperative language learning is an instructional method that give a chance for students to exchange different learning skills and techniques, learn from each other.The paper shows that the concept of cooperative language learning,that effectively used in the process of learning language and it can provide students with necessary  social and academic skills.